Date Journalism or Journalism as a New Genre of Data Media (Herald of Journalism, 2016)
The article is devoted to the formation of a new direction in Kazakhstan’s modern journalism, in particular, data-journalism and journalism education in the country date on the example of foreign experience, the development prospects of the date of journalism.
Keywords: data journalism; journalism data; infographics; information processing; education; journalism; the date; the profession of journalism